Perancangan Umbrella Energy Sebagai Charger Handphone Pada Cafe - Wahyu Ferdiana Octavian; Rahmat Hidayat; Lela Nurpulaela (Department of Mechanical Engineering, University of Udayana, 2020)
Batteries and solar panels are 2 device capable of converting sunlight into unidirectional electrical energy. The power of the energy stored from the battery can be converted into AC or DC current. A canopy umbrella covered with solar panel elements can be used as a mobile phone charger center as well as a place to relax. Umbrella which are a source of DC electrical energy are desaigned to follow existing products in the market with additional modifications in the form of new renewable energy (EBT) or by another nama environmentally friendly energy. This tool is named as umbrella energy, with the use of solar panels used at 90 Wp (Wattpeak), it can produce an average output power of 28.49 W hour. The system will generate maximum power for charging to the battery in 1 day of 227.99.